(untitled) (Research, Society and Development, 2021)
Objective: To analyze the factors that influence mothers in vaccination adherence. Methodology: Qualitative, exploratory and descriptive research, carried out with 18 mothers who use a Basic Health Unit. Data were collected through interviews supported by a script, these were transcribed and submitted to thematic analysis. All current ethical precepts were followed. Results: 18 women, aged between 20 and 39 years, participated in the study. The mothers emphasize that the main benefit of vaccination is the prevention and protection for some communicable diseases, in relation to possible harm they emphasize that the benefits outweigh them. Regarding the impacts of reduced vaccination coverage, the mothers in this study point out that there may be an eminence of their children to contract contagious infectious diseases due to the immunological gap that would be supplied by the vaccine. Conclusion: The study identified that mothers are the main responsible for the vaccination of children, and the main factor for vaccine adherence is the prevention and protection for some communicable diseases. Participants report that the benefits of immunization outweigh the harm, and these are related to the possibility of adverse effects, and pain during the invasive procedure.